Strategi Komunikasi Pemasaran Online Shop Brand Mabello Melona dalam Menarik Minat Konsumen di Makassar - Fahmi Adiba; Nahdiana Nahdiana; Pramudita Budi Rahayu (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2021)
This study aims to analyze the marketing communication strategies of online shops employed by Mabello Melona inincreasing customers' interest in purchasing Mabello products. This is descriptive qualitative research by investigatingfacts. Data were obtained through interviews and observations of informants which were analyzed by a triangulationmethod. The result showed that Mabello Melona's marketing communication strategies employed Instagram and Tik Toksocial media and use a Shoopee marketplace application as the main sakes medium. In addition, this brand also advertised itsproduct in Instagram ads, and Tik Tok ads, and used endorsements from local and national public figures. Meanwhile, salespromotion efforts are carried out by providing giveaways, discounts, and package sales.